Ways to gain influence for residents in two gentrifying neighbourhoods: a comparison between Tøyen in Oslo and Lavapiés in Madrid - Reichborn-Kjennerud, Kristin; Ruano de la Fuente, José Manuel; Sorando, Daniel (Papeles de Población, 2022)
In gentrifying cities, entrepreneurial strategies often conflict with the interests of citizens. Cities deal with this differently. Participatory democracy is one method to avoid conflict through increased responsiveness to citizens. Participatory processes are nevertheless particularly challenging in central neighbourhoods where the problems of gentrification are most acute. In the present study, we sought to understand how these participatory processes play out differently depending on the participatory system, the economic situation and the local capacity for collective action. Towards this goal we compare two deprived neighbourhoods that face these type of problems in the north and south of Europe, Oslo, Norway and Madrid, Spain.